Diskriminasi terhadap perempuan korban kekerasan seksual di Kabupaten Banyumas dalam prespektif religiusitas - Elisabeth Febrianan Daniputri Harnowo; Elly Kristiani Purwendah; Wiwin Muchtar Wiyono; Ikama Dewi Setia Triana (Yinyang: Jurnal Studi Islam Gender dan Anak, 2023)
The rate of sexual violence is increasing every year. Many cases of sexual violence stop midway or are only resolved at the mediation level. Even though normatively this has been completed, the victim's right to protection does not apply to living his or her life again in society. This research focuses on the response and role of religious figures in handling cases of sexual violence. This research uses a Normative Sociological approach method. The assumption that the victim's way of dressing and behaving was the trigger for this action this continued until discrimination emerged against women victims of sexual violence.